Racial preferences in three social contexts a comparison among primary, intermediate and college students.[article]. - Watanabe, Fumio
The presents study aims to explore the racial preferences of Filipinos in three social contexts, namely: study, play, and home. Subjects from Quezon City and Tanay, Rizal Philippines were shown sets of colored pictures depicting faces of children from various nationalities. The odor of preferences and reasons for said preferences were obtained. Filipino children showed an increasing degree of heterogeneity of racial preferences as age increases, The results of the study were explained in terms of relative exposure to other races, developmental stages and social learning principles.